2014
DOI: 10.2174/1875399x01407010141
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Physical Education Teachers’ Discourses on Learning How to Become a Teacher: [Re]Constructing a Professional Identity Based on Visual Evidence

Abstract: Identity has been used as an analytical tool to capture how teachers work, learn and develop professionally. This paper takes chiefly Gee's [1] discursive notion of identity to examine the discourses that pre-service physical education teachers used about themselves and others in discussing their teaching practices in the context of their practicum training in school. More specifically, this study aims to identify and characterize the situations of concern [roles, individuals, groups, events, meanings] to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
(192 reference statements)
0
15
0
Order By: Relevance
“…Keating et al (2017) pointed out that PETE is unlikely to change PE teacher identity unless specific identity-related interventions are embedded in the programme. Previous studies have reported that central supportive elements of PETE in professional identity formation in general include practicum (Alves et al, 2012;Da Cunha et al, 2014) and social recognition from colleagues, instructors (Alves et al, 2012;Da Cunha et al, 2014;Sirna et al, 2010) and parents (González-Calvo and Fernández-Balboa, 2018). Furthermore, students' emotions reportedly play an important role in supporting and guiding the professional identity construction process (Alves et al, 2018).…”
Section: Teacher Educationmentioning
confidence: 96%
“…Keating et al (2017) pointed out that PETE is unlikely to change PE teacher identity unless specific identity-related interventions are embedded in the programme. Previous studies have reported that central supportive elements of PETE in professional identity formation in general include practicum (Alves et al, 2012;Da Cunha et al, 2014) and social recognition from colleagues, instructors (Alves et al, 2012;Da Cunha et al, 2014;Sirna et al, 2010) and parents (González-Calvo and Fernández-Balboa, 2018). Furthermore, students' emotions reportedly play an important role in supporting and guiding the professional identity construction process (Alves et al, 2018).…”
Section: Teacher Educationmentioning
confidence: 96%
“…Two further core categories were identified relating to developing student teachers' sense of identity (four papers) and creating learning communities (eight papers). Relational attributes were identified as important for helping to create an environment where student teachers can be guided and supported to develop their teaching abilities, whilst developing in a learning community (Faucette and Nugent, 2012;Young and MacPhail, 2016;da Cunha et al, 2014). Albuquerque et al (2014) suggest that a supportive developmental process helps to nurture a sense of identity in the student teacher.…”
Section: Attributes Of Mentorsmentioning
confidence: 99%
“…TI has been defined as a person's lived experiences and stories around dominant discourses in several areas: personal beliefs (MacDonald, 1998; MacDonald and Kirk, 1999), physical education pedagogies and learning (Wrench and Garrett, 2012), sport-related discourses (Dowling, 2011; Garrett and Wrench, 2007; MacDonald and Kirk, 1999; Virta et al, 2019), and physicality (Garrett and Wrench, 2007; MacDonald and Kirk, 1999; Virta et al, 2019). From a symbolic interactionist perspective, TI includes a set of labels and categories identified by PPETs, which are also recognized by others (Alves et al, 2012; da Cunha et al, 2014; Fletcher, 2012; Fletcher et al, 2013). Only two studies were based on theories concerning TI and action, where TI referred to PPETs' identification with the role of a teacher, which became the salient part of their selves, informing and guiding their intentions and behaviors in teaching (Faulkner et al, 2004; Solmon et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…While the ongoing, reflexive, and fluid features of TI in a specific context have been explored in these studies, the stable, enduring, and universal features of TI have been overlooked (Keating et al, 2017). So far, only one study has investigated the characteristics of PPET-TI (da Cunha et al, 2014), which provided a detailed and rich narrative answer to identity questions such as “who am I?” and “what do I do?”(Gee, 2000). Although we acknowledge the importance of understanding how TI forms and develops, researchers first need to have a certain level of agreement on what constitutes TI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation